Kinetic analysis to describe Co-operative redox enhancement effects exhibited by bimetallic Au–Pd systems in aerobic oxidation. Issue 1 (16th November 2022) - Daniel, Isaac T.; Zhao, Liang; Bethell, Donald; Douthwaite, Mark; Pattisson, Samuel; Lewis, Richard J.; Akdim, Ouardia; Morgan, David J.; McIntosh, Steven; Hutchings, Graham J.
Abstract : Recent work has demonstrated that, for bimetallic Au–Pd systems, the rate of catalytic alcohol and formyl dehydrogenation (DH) is intrinsically linked to the rate of oxygen reduction (ORR) within the same system. Abstract : Recent work has demonstrated that for bimetallic Au–Pd systems, the rate of catalytic alcohol and formyl dehydrogenation (DH) is intrinsically linked to the rate of oxygen reduction (ORR) within the same system. Herein, the rate enhancement as a result of the coupling between these two processes is assessed via kinetic analysis for the oxidative dehydrogenation of 5-hydroxymethylfurfural. The influence of the Au and Pd molar ratio is explored for a physical mixture of carbon-supported catalysts by changing the mass of each 1 wt% catalyst. Importantly, the activity of the bimetallic system exceeds the sum of the monometallic analogues, at all molar ratios. It is shown that by considering the coupling between two individual reactions (DH and ORR), the kinetic analysis of the system predicts where the maxima in monometallic and bimetallic activity will be observed. The accuracy of the model provides further evidence and understanding of cooperative redox enhancement (CORE) effects observed in bimetallic, heterogeneous catalytic systems.